2012
DOI: 10.1002/bit.24561
|View full text |Cite
|
Sign up to set email alerts
|

Biodefluorination and biotransformation of fluorotelomer alcohols by two alkane‐degrading Pseudomonas strains

Abstract: Fluorotelomer alcohols [FTOHs, F(CF(2))(n) CH(2)CH(2)OH, n = 4, 6, and 8] are emerging environmental contaminants. Biotransformation of FTOHs by mixed bacterial cultures has been reported; however, little is known about the microorganisms responsible for the biotransformation. Here we reported biotransformation of FTOHs by two well-studied Pseudomonas strains: Pseudomonas butanovora (butane oxidizer) and Pseudomonas oleovorans (octane oxidizer). Both strains could defluorinate 4:2, 6:2, and 8:2 FTOHs, with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
72
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 41 publications
17
72
1
Order By: Relevance
“…19 6:2 FTOH soil biotransformation pathways were described in detail 19 and were later confirmed by pure Pseudomonas bacterial culture. 41 In this study, PFPeA and 5:3 acid were observed as two abundant products, consistent with a previous soil biotransformation study with 6:2 FTOH 19 and further confirming that the 6:2 FTOH route was operational in soil dosed with 6:2 FTI. However, PFBA was not observed, and the PFHxA level was less than half of that in soil dosed with 6:2 FTOH ( Table 1), suggesting that part of the 6:2 FTOH route may have been diverted toward the putative 6:2 FTUI route in soil dosed with 6:2 FTI, producing significant amounts of PFHpA.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…19 6:2 FTOH soil biotransformation pathways were described in detail 19 and were later confirmed by pure Pseudomonas bacterial culture. 41 In this study, PFPeA and 5:3 acid were observed as two abundant products, consistent with a previous soil biotransformation study with 6:2 FTOH 19 and further confirming that the 6:2 FTOH route was operational in soil dosed with 6:2 FTI. However, PFBA was not observed, and the PFHxA level was less than half of that in soil dosed with 6:2 FTOH ( Table 1), suggesting that part of the 6:2 FTOH route may have been diverted toward the putative 6:2 FTUI route in soil dosed with 6:2 FTI, producing significant amounts of PFHpA.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…For a test system with simple components and weak matrix interference, such as a pure bacterial culture, a straightforward water-miscible solvent extraction (WMSE) plus centrifugation and filtration procedures would be sufficient to obtain a representative sample extract for further instrumental analysis [31]. This was done by adding an equal or slightly larger volume of a solvent (e.g., acetonitrile) to the bacterial liquid culture medium to extract precursors and transformation products.…”
Section: Sample-extraction Methodsmentioning
confidence: 99%
“…Soil is the primary deposit medium of volatile precursors through atmospheric deposition, while sewage sludge and river sediment are important sinks of PFASs in aqueous systems from household and industry emissions [15][16][17]. To obtain knowledge on the specific microorganisms responsible for the polyfluoroalkyl precursor biotransformation processes, microbial consortium or pure bacterial cultures from soil and sewage sludge were isolated and used [30][31][32]. To elucidate the metabolism mechanism and possible adverse effects due to covalent binding of unsaturated polyfluoroalkyl intermediate metabolites to biological macromolecules, in-vitro bioassays were performed using hepatocytes, cytosol fractions and liver microsomes from mammalian and fish species [19,21].…”
Section: Test Systemmentioning
confidence: 99%
“…For example, Wang et al (2011) detected PFBA formation (accounting for approximately 0.14% mol/mol) when 6:2 FtS was aerobically oxidized, 24 whereas production of PFBA was also observed when 6:2 FtOH was biotransformed under aerobic conditions. 23,25,26 In this study, PFBA accounted for approximately 0.1% (mol/mol) of the total amended 6:2 FtTAoS at the end of the incubation. It is possible that 8:2 FtS biotransformation also produced the C n−2 PFCA product, PFHxA, as aerobic 8:2 FtOH biotransformation to PFHxA has been previously observed.…”
Section: Environmental Science and Technologymentioning
confidence: 99%